Is that traditional? Contexts, geographies and musical trajectories in the construction of a notion about what is «traditional». The case of Trío Los Cholos in the city of Lima - Molina Palomino, Pablo Alberto (Pontificia Universidad Católica del Perú, 2018)
The present article exposes the results of a research project developed between 2011, 2012 and 2016 with Trío Los Cholos in the city of Lima, in which I sought to problematize the sense and use given to the notion of «traditional» within the musical practice of the ensemble, in interaction with its performance contexts. Our departure point was not to consider such term as an objective trait, characteristic of a variety of cultural artifacts according to authenticity rhetorics or academic folklore theories, but as an abstract principle constructed based on a set of meanings, perceptions or valuations defined by the ensemble’s performers. In this sense, it is not sought to determine what is «traditional» but which processes operate to determine the applicability of that category and the actors involved in them. To do this, we reconstructed the life histories of the members of the ensemble and conducted controlled sessions of musical exposition. This allowed us to observe that what we understand as «traditional» responds to a process that starts from the identification of sonorities and styles, which in turn activates representations of place associated to musical geographies and abstract performance contexts.